Analysis of the behavior of geotextile reinforced slopes with different kinds of foundations, backfills and inclinations with finite elements method - Dosay, Serhat. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Geotextiles have developed into common materials on many retaining wall and embankment projects throughout the world. This widespread acceptance of geotextiles is a result of thousands of successful installations, many comprehensive research studies, and proven economical benefits derived from their use. In this project, eighteen different analyses of geotextile reinforced slopes with the combination of three kinds of foundation, two kinds of backfill material and three kinds of inclination, were conducted by means of finite elements program PLAXIS. In the analyses, a model similar to the study of San, Leshchinsky and Matsui (1994) is used. In this program, six node triangular elements and two dimensional plain strain model is considered. The backfill material is modeled by Hardening soil model and the foundation is modeled by Mohr- Coulomb model. The stage construction method of Plaxis is used in the model and 50 cm layers were considered during stage construction. Also Phi-c reduction procedure was carried out for the safety analysis. The effects of using different parameters in the structure were determined.
Keywords: Geotextiles.